BRICS COUNTRIES IN GLOBALIZATION PROCESSES - Sergey Lunev (Сравнительная политика)
Globalization remains the crucial trend of global development, and it is especially evident in economic sphere. Apart from it, political, informational and cultural globalizations are actively discussed. The rapid development of global market, initiated by the West, paradoxically, fostered redistribution of economic influence towards the non-Western countries and primarily to Asia. Therefore, the record of participation of BRICS states (China and India, primarily) in global processes is instructive. These two countries achieve significant developmental successes due to their integration in world economy without abandoning active participation of their government in regulation of economic and social activities. Analysis of the strategies adopted of other BRICS countries could appear quite useful for Russia.